Multi-locus high-risk alleles association from interleukin’s genes with female infertility and certain comorbidities - Khalil Khashei Varnamkhasti; Samire Khashei Varnamkhasti; Najmeh Bahraini; Mohaddeseh Davoodi; Mahsa Sadeghian; Massomeh Khavanin; Raana Naeimi; Sirous Naeimi (BMC Research Notes, 2024)
Abstract Objective There is evidence that cytokine genes’ single nucleotide polymorphisms could be the reasons behind female infertility. This study aimed to identify the role for Interleukin33 rs1048274 (G > A) and rs16924243 (T > C), Interleukin22 rs1397852121 (C > T), rs1295978671 (C > T) and rs2227483 (A > T), Interleukin17A rs2275913 (G > A,C) and Interleukin17F rs763780 (T > C), Interleukin13 1512 (A > C) and IL13 2044 (G > A), and Interleukin4 rs2243250 (C > T) and rs2070874 (C > T) gene polymorphisms in female infertility to gain a richly more detailed understanding of its genetic predisposition. Five distinct groups, each comprising 200 infertile women and 200 age-matched fertile controls, were recruited to each Interleukins (33, 22, 17, 13 and 4) in this case–control study and were genotyped by using an amplification refractory mutation system. Statistical analysis is conducted by SPSS software V. 22 and using Chi-square (χ2) and logistic regression tests. Strength of association was estimated by multiple-comparison correction, population structure test and Haplotype analysis. The study was approved by the Academic Ethics Committee and each enrolled patient signed an informed consent. Results Our statistical results revealed risk alleles in all of the substitution lines for women infertility. Current findings provided evidence that in the presence of Interleukin33 A p-value rs1048274 = 0.002 and C p-value rs16924243 < 0.0001, Interleukin 22T p-value rs1397852121 < 0.0001 and T p-value rs2227483 = 0.000, Interleukin17A A p-value rs2275913 = 0.003 and Interleukin17F C p-value rs763780 = 0.000 and Interleukin13 C p-value 1512 = 0.000 and A p-value 2044 = 0.003, Interleukin4 T p-value rs2243250 = 0.001 and T p-value rs2070874 = 0.009 risk alleles, risk genotype also were significantly associated with increased chances of developing infertility. The relationship between risk genotypes and several well-established infertility risk factors including, polycystic ovary syndrome, premature ovarian failure, oophorectomy, diminished ovarian reserve, endometriosis, uterine fibroids, ovarian cysts, uterine polyps, fallopian tube blockage and thyroid dysfunction, also exhibited. This study suggests the significant role of interleukin gene polymorphisms in human reproductive success.